2015
DOI: 10.1097/phh.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Agencies' Level of Engagement in and Perceived Barriers to PHAB National Voluntary Accreditation

Abstract: Accreditation is expected to provide pathways to accountability, consistency, and better fit between community needs and public health services. National strategies targeting rapid diffusion of accreditation among public health agencies should include elements that address the needs of LHDs with varying degrees of intent to pursue accreditation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…In 2011 the Public Health Accreditation Board (PHAB) initiated a national voluntary accreditation process. 6,7 As of November of 2016, 142 local health departments have been accredited by PHAB. 8 The accreditation process requires that each LHD complete a series of tasks from several accreditation domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011 the Public Health Accreditation Board (PHAB) initiated a national voluntary accreditation process. 6,7 As of November of 2016, 142 local health departments have been accredited by PHAB. 8 The accreditation process requires that each LHD complete a series of tasks from several accreditation domains.…”
Section: Introductionmentioning
confidence: 99%
“…For example, existing studies have found that LHD accreditation pursuit has been associated with formal quality improvement programming, and that the implementation of accreditation can be facilitated by financial and legal incentives, population size, degree of top executive, governance structure, state health department accreditation pursuit, and the existence of formal quality improvement initiatives. 9,10,11,12 …”
Section: Introductionmentioning
confidence: 99%
“…One of those factors is the role of the governing entity, which for many LHDs is a local board of health (LBoH). 3 …”
mentioning
confidence: 99%
“…3 The PHAB accreditation standards and measures directly address the important role of governing bodies; they include standards dedicated to “engagement with the governing entity” and requirements for the governing body to indicate approval for the initial accreditation application and to participate in the site visit. 4 Therefore, LBoHs are potentially important allies in motivating LHDs to pursue PHAB accreditation, 3 but the extent to which LBoHs play this role has been unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation